ANALISIS YURIDIS SENGKETA ADMINISTRATIF ATAS TANAH BERUPA PEMBATALAN SERTIFIKAT HAK MILIK DESA SELAYANG (STUDI PUTUSAN NOMOR 327 K/2016/PTUN.MEDAN) - WAHYU UTAMA PUTRA NASUTION (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Muhd Yamin, SH, MS2. Prof. Dr. Syafruddin Kalo, SH, MHum3. Dr. Edy Ikhsan, SH, MA A certificate is issued to insure the benefits of the right owner in accordance with the juridical and physical data that have been registered or recorded in the land registry. Land title certificate is useful for the right owner to the third party that they are the owner of the land concerned. The example of this problem is the Case in the Verdict No. 327 K/2016/PTUN. The objective of the research is to find out the causes of the issuance of Land Title Certificate in Selayang Village, the legal protection for the plaintiff against the issuance of the land title certificate, and the judge’s legal consideration in pronouncing the case in the Verdict of the Supreme Court. This thesis employs normative juridical research with analytical description. It is concluded that the legal consideration of the Panel of Judges concerning this case is that Medan State Administrative Court has revoked its Ruling. The Ruling of Medan State Administrative Court is expected to provide legal certainty for the status of the legal object and the land, similar to the case which states that the Plaintiff wins at the level of Cassation and annuls the Land Title Certificate.Keywords: Administrative Dispute, Legal Protection, Judge’s Consideratio